The Effect of The Tangram Media Assited STAD Model on The Understanding Of Mathematics Concepts Of Flat Building Materials - Viainda Sari; Tria Mardiana; Septiyati Purwandari (Prosiding University Research Colloquium, 2021)
This study aims to determine the effect of the STAD model assisted by tangram media onthe understanding of mathematical concepts in fourth grade students of SD Muhammadiyah Integratif Dukun, Magelang Regency.This research is a type of pre-experimental research with one group pretest-posttest design. The research was selected by saturated sampling. The samples taken were 19 students. The method of data collectionis done by using a description test. The validity test uses the product moment formula,while the reliability test uses the Cronbach alpha formula which produces a reliabilityindex of 0.924. Data analysis used parametric statistical techniques, namely the PairedSample T-Test with the help of the SPSS for Windows version 25.00 program.The resultsof the analysis of the Data Test of Two Dependent Samples which were carried out usingthe Paired Sample T-Test with the t count > t table, namely 18.323 > 2.093 with the Asympvalue. Sig. (2-tailed) 0.000 < 0.05. Based on the results of the analysis and discussion, thereis a difference in the average score of the mathematical concept understanding test, namelythe pretest average of 50.46, while the posttest average is 80.02. This shows that there isan effect of the STAD model assisted by tangram media on the understanding of themathematical concept of flat shape material in fourth grade students of SDMuhammadiyah Integratif Dukun, Magelang Regency, Academic Year 2020/2021.